Molecular regulation of pepper innate immunity and stress tolerance: An overview of WRKY TFs. (October 2019) - Hussain, Ansar; Noman, Ali; Khan, Muhammad Ifnan; Zaynab, Madiha; Aqeel, Muhammad; Anwar, Muhammad; Ashraf, Muhammad Furqan; Liu, Zhiqin; Raza, Ali; Mahpara, Shahzadi; Bakhsh, Ali; He, Shuilin
Abstract: The WRKY transcription factors (TFs) family constitutes a major group of TFs in spermatophytes. Different studies have endorsed the considerable biological roles performed by WRKY TFs in plant growth, biotic and abiotic stress responses. Genomic and transcriptomic profiling facilitate us in understanding the WRKY genes in various plants and reveal how WRKY TFs perform their action in response to different plant stresses. WRKY TFs actively take part in metabolism including carbohydrate synthesis, senescence, and secondary metabolites production. Molecular organization of WRKY TFs in plants highlight most predicted outcome of multiple responses simultaneously. Repression and activation related to W-box and other such elements is controlled at transcriptional, translational and domain level. WRKY TFs are becoming more important in crop improvement because of their binding with downstream elements. Additionally, WRKY proteins intermingle with various other TFs for modulating plant immunity. However, WRKY TFs self-regulation and crosstalk between different signaling pathways using WRKY TFs still need extensive investigations. In this review, we focused characteristics of WRKY TFs in Capsicum annum and related research advancement on their functional involvement in plant responses to the challenges of high temperature stress and pathogens infection. We summarized information about Capsicum annum WRKY TFs on the basis of their functions, their target genes and signaling pathways. Moreover, the mechanisms for synergistic responses to various biotic and abiotic stresses, WRKY target genes and other TFs as well will be of more interest with increments in existing information. Highlights: WRKY TF family has significant role in plant life cycle and survival. Repression and activation related to W-box and other such elements is controlled at transcriptional, translational and domain level. The expression of some WRKY TFs may be perturbed by compatible or incompatible interactions between plants and microbes. We summarized information about CaWRKYs on the basis of their functions.